Managing Nitrogen Inputs and Outputs on a Dairy Farm - Rebecca Hellmuth; George Hochmuth (EDIS)
In dairy production systems, nitrogen flows through both the forage crops and the dairy cows. Forage crops use nitrogen mineralized from manure for plant growth. Harvested crops are then fed to dairy cows that, in turn, use the nitrogen for their growth and milk production. When the cows excrete a portion of the consumed nitrogen as manure the cycle is renewed. This 5-page fact sheet focuses on the forage production aspect of the nitrogen cycle at a dairy farm. Written by Rebecca Hellmuth and George Hochmuth, and published by the UF Department of Soil and Water Science, March 2015. (Image credit: R. Hellmuth)